Linking small-scale farmers to the durum wheat value chain in Ethiopia: Assessing the effects on production and wellbeing. (August 2018) - Biggeri, Mario; Burchi, Francesco; Ciani, Federico; Herrmann, Raoul
Highlights: The project's impacts were positive farmers' productivity increase through a cooperative-centred strategy. The cooperative-centred strategy determined an inclusive durum wheat value chain development. The project's impacts were positive for different categories of farm size. The changes induced by project seemed not to have occurred at the expense of rotation practices. Abstract: Food security and agricultural-led industrialisation are pivotal development objectives in Ethiopia. One of the main challenges this country faces is increasing agricultural productivity by integrating smallholder farmers into a high-value agricultural commodity supply chain. This paper examines an integrated project—the Agricultural Value Chains Project in Oromia (AVCPO)—that aims to improve the livelihoods of smallholders in the Bale Zone by involving them in the production of high-quality durum wheat and linking them to the pasta industry via farmers' cooperatives. Using primary data collected in 2014 and retrospective information, this paper investigates the AVCPO's effects on the quantity of cereal production, the share of cereals that have been sold through cooperatives, food security, and education. In order to account for potential violations of the exclusion restriction assumption, an instrumental variable approach is applied, together with three additional estimation strategies. The results suggest that the project has had a large and positive effect on gross and net values of cereal production per hectare, as well as on the share of production sold to pasta makers through cooperatives. These benefits accrue equally to land-rich and land-poor farmers. Furthermore, our analysis suggests that the AVCPO has improved educational outcomes and reduced food insecurity, without affecting crop rotation practices. Overall, our findings point to the effectiveness of the project. Before replicating or scaling up this intervention, however, it is necessary to understand how to better involve poorer farmers and which adjustments are needed if the areas selected have a lower potential than Bale Zone.